A longitudinal evaluation of e-government at the local level in Greater Western Sydney (GWS) Australia - Fan, Qiuyan (2018)
This research reviews and revisits the 14 local government websites to determine whether the GWS councils have improved their online services since 2009. The study has found that there have been significant developments and improvements in e-government services among the GWS councils, while these have been variable and in many cases there is scope for further improvement. This research is significant as a longitudinal evaluation can track the evolutionary paths of local e-government development and provides insights into the challenges and opportunities of e-government development at the local level in Australia. - Reproduced.
Keywords: Electronic governance; Local government - Australia - Sydney